Field Research When There Is Limited Access to the Field: Lessons from Japan. Issue 1 (11th January 2023) - Amano, Kenya; Dominguez, Melanie Sayuri; Fraser, Timothy; Gagnon, Etienne; Incerti, Trevor; Jang, Jinhyuk; McClean, Charles T.; Mitchell, Austin M.; Miyano, Sayumi; Moreshead, Colin; Saijo, Harunobu; Stanescu, Diana; et al.
ABSTRACT: How can scholars conduct field research when there is limited access to the field? This article first identifies how limited and uncertain field access can affect field research and then provides recommendations to address these challenges. We focus on conducting field research in Japan because of our substantive expertise, but we believe that the problems and solutions outlined in this article are applicable to a broad range of countries. Our hope is that this article contributes to the developing literature on conducting research during times of emergency and to the larger literature on best practices for field research.